Dissemination of CTX-M-Producing Escherichia coli in Freshwater Fishes From a French Watershed (Burgundy) - Bollache, Loic; Bardet, Emeline; Depret, Géraldine; Motreuil, Sébastien; Neuwirth, Catherine; Moreau, Jérome; Hartmann, Alain (Frontiers in Microbiology, 2019)
The burden of extended-spectrum β-lactamases producing Escherichia coli (ESBL-Ec) has increased since several decades. Freshwater ecosystems are suspected to play an important ecological and evolutionary role in driving the emergence, persistence and dissemination of antimicrobial resistance. The aim of our study was to decipher the occurrence of ESBL-Ec in a small watershed (Ouche river, Burgundy) targeting environmental matrices and fishes. Among cefotaxime resistant E. coli (ctxR Ec) isolates, we detected and characterized 36 ESBL-Ec from water, biofilm and fish guts. ctxR Ec and ESBL-Ec were found in samples from sites located downstream the first small town within the watershed studied. Treatment of urban wastewater by waste water treatment plants (WWTP), might thus be a major potential source of ctxR Ec and thus of ESBL-Ec. Prevalence of total E. coli and ctxR Ec in fish gut ranged between 0 to 92 % and 0 to 85%; respectively, depending on the sampling site and the fish species. Fish diet (predator or omnivore) seemed to influence strongly the prevalence of total E. coli and ESBL-Ec. Extended spectrum beta lactamases produced by the isolates from this study belonged to the CTX-M family (CTX-M group 1 and 9). Moreover, some environmental ESBL-Ec proved to share genotypic features (MLST types) with isolates originated from 8 WWTP effluents discharged in the Ouche river and with clinical isolates (i.e. sequence type ST131). Ninety seven % of ESBL-Ec from the study harbour additional antibiotic resistances, and can thus be considered as multi drug resistant (MDR) bacteria. Finally, 53% of the ESBL-Ec strains harbour sequences identical to class1 integron-integrase (intl1). These results are discussed in the perspective of defining indicators of antibiotic resistance contamination in freshwater ecosystems.